(untitled) (World Bulletin of Social Sciences, 2024)
This article provides instructions on the influence of heredity, environment and upbringing on the development of a mature and wellrounded personality of a person, as well as measures to form child and society, social relations, social status and norms of behavior in the process of socialization.